CRC handbook of phase equilibria and thermodynamic data of copolymer solutions - Wohlfarth, C. (CRC Press, 2011)
"Packed with newly published references, this book provides 150 new vapor-liquid equilibrium data sets; and includes 50 new tables with classical Henry's coefficients. It also contains 250 new liquid-liquid equilibrium data sets, 350 new high-pressure fluid phase equilibrium data sets; 70 new data sets describing PVT properties, densities, or excess volumes; as well as 40 new enthalpic data sets. A larger data table for values of second osmotic virial coefficients and topics such as include vapor-liquid equilibrium data and gas solubitilities of copolymer solutions round out the coverage"--